Integrating Adat Law in Indonesia: Challenges and Opportunities in a Centralized Legal Framework - Hakim, Lukman; Melati, Qatrunnada Hamparan; Negara, Purnawan Dwikora (Universitas Negeri Semarang, 2025)
This study examines the integration of adat law into Indonesia’s national legal framework, focusing on the challenges and opportunities arising from the country’s legal pluralism. The objectives are threefold: to assess the historical and constitutional challenges in recognizing adat law, analyze the impact of post-Reformasi democratization, and compare Indonesia’s experience with other multi-ethnic nations. The primary problem lies in the centralist 1945 Constitution, which prioritizes state law over adat law, limiting the latter's recognition and application. The study finds that, despite constitutional amendments aimed at decentralization, adat law continues to face marginalization due to inconsistent regional regulations and the central government’s overriding legal authority. Post-Reformasi democratization has allowed for greater local governance, but the integration of adat law remains conditional and fragmented across regions. Comparative analysis with countries like Canada and South Africa reveals that a constitutional framework recognizing indigenous laws, alongside judicial clarity, can enhance legal pluralism. The study underscores the need for constitutional reforms and comprehensive judicial guidelines to ensure the full integration of adat law. This would create a more inclusive legal environment that respects Indonesia’s diverse cultural and legal traditions while promoting justice and equity for adat communities.